SISTEM AKUSTIK PADA INTERIOR KAPEL RUMAH SAKIT KATOLIK VINCENTIUS A PAULO DI SURABAYA - Wardani, Laksmi Kusuma; Kumalasari, Yovita (Dimensi Interior, 2008)
A Chapel is a small church where Catholics worship God. The quiet, silent and comfortable atmosphere for worshiping depends on the acoustic quality of the room that can support worshiping activities such as praying, singing and listening to the priest’s sermon. An interior designer has an important role in creating an atmosphere suitable for worship in the chapel. The criterion of a good and suitable acoustic system in a chapel is influenced by shape of the lay out, the absorbsing materials used and the acoustic tools. An Acoustic parameter determines the quality of acoustics used in order to avoid disturbances caused by poor acoustic systems. Abstract in Bahasa Indonesia: Kapel merupakan tempat beribadah untuk umat katolik. Untuk menciptakan suasana ibadah yang hening, syahdu dan nyaman tergantung atas kualitas akustik ruang sehingga umat dapat berdoa, memuji Tuhan dan mendengarkan firman dari pastor dengan khidmat. Perancang interior berperan dalam menciptakan suasana khidmat dalam kapel. Kriteria akustik yang baik dalam suatu kapel dipengaruhi bentuk denah, bahan penyerapan yang digunakan dan alat akustik yang baik. Parameter akustik menentukan kualitas akustik yang digunakan agar tidak mengakibatkan kecacatan akustik yang mengganggu lingkungan sekitar. Kata kunci: Sistem Akustik, Interior, Kapel